Everybelly - Lam, Thao (Groundwood Books : House of Anansi Press, 2025)
Maddie and her mom spend a sunny day at the local public pool where she meets and greets friends and neighbors. Maddie is waist-high on most of them, and she knows there's an interesting person behind every belly she passes -- like Jackie, the artist with a splatter of ice cream across their belly. Maddie's splatter painting often leaves Mama speechless, too! The poolside belly parade keeps Maddie musing: How bellies can make excellent tables, how hard some people work to keep their bellies flat when Maddie prefers her belly full, and how you should never, ever stick your hands in other people's bellies, no matter how soft and doughy they might look. (Maddie's cat taught her that the hard way.) As Maddie dances, swims and makes the long climb up to the diving board, Thao Lam's celebrated cut-paper collage portrays bellies and bodies of all shapes and sizes -- bellies with scars, tattooed bellies, growing bellies, growling bellies, bellies with six-packs, stretch marks, insulin monitors, freckles and more -- proving that every belly deserves its place in the sun.